Cooperative Learning Team Game Tournaments (TGT) On Literacy and Numeracy Abilities of Early Childhood - Ni Made Ari Sugiartini; I Ketut Gading; I Gede Astawan (Journal of Education Action Reseach, 2025)
Early childhood literacy and numeracy skills remain a challenge in kindergarten learning due to the lack of application of innovative and engaging learning models. This study aims to investigate the impact of the Team Game Tournaments (TGT) cooperative learning model on enhancing early childhood literacy and numeracy skills. This type of research is a quasi-experimental study with a Nonequivalent Control Group Design. The subjects of the study consisted of 67 children from group B in two selected kindergartens, chosen through cluster random sampling techniques. Data were collected using observation and testing techniques to assess literacy and numeracy skills, utilizing validated instruments. Data analysis was conducted using the MANOVA test with the assistance of the SPSS application at a significance level of 0.05%. The results of the study showed that (1) there is a significant effect of the TGT model on literacy skills, (2) there is a significant effect of the TGT model on numeracy skills, and (3) there is a significant effect of the TGT model on literacy and numeracy skills simultaneously. These findings confirm that the game-based cooperative learning approach is efficacious in improving the basic cognitive abilities of early childhood. The implications of this research highlight the importance of integrating the TGT model in learning to support the development of holistic literacy and numeracy.